2020
DOI: 10.1155/2020/7131590
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Three Radiotherapy Techniques in Irradiation of Left-Sided Breast Cancer Patients after Radical Mastectomy

Abstract: Introduction. This study is aimed at evaluating the dosimetric differences among target segmented planning (TSP), conventional 9-field intensity modulated radiation therapy (9FIMRT) planning, and volumetric modulated arc therapy (VMAT) planning for postmastectomy radiotherapy of left-sided breast cancer patients. Material and Methods. Fifteen left-sided breast cancer patients who underwent radical mastectomy were enrolled. In TSP, the planning target volume (PTV) was divided into four regions (supra/infraclavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
2
9
1
1
Order By: Relevance
“…These OARs were protected by adjusting the priority values to reduce the maximum percent dose and scatter dose. Compared with our IMRT plans and other studies of VMAT plans, the mean dose to the heart was comparably lower in our VMAT plans, 5.2 ± 0.9 Gy, while it was 13.5 ± 5.0 Gy according to Zhang [ 17 ], 7.2 ± 2.3 Gy according to Zhao [ 18 ], 9.31 ± 1.62 Gy according to Hu [ 19 ], 11.9 ± 5.06 Gy according to Ma [ 20 ], 7.7 ± 1.1 Gy according to Xie [ 21 ] and 7.4 ± 1.4 Gy according to Wang [ 22 ],15.2 ± 2.2 Gy according to Nobnop [ 24 ], 9.3 ± 1.1 Gy according to Zhang [ 26 ]. The low and medium doses received by the heart were also significantly lower with the VMAT technique than with the IMRT technique, except for V 2.5 .…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…These OARs were protected by adjusting the priority values to reduce the maximum percent dose and scatter dose. Compared with our IMRT plans and other studies of VMAT plans, the mean dose to the heart was comparably lower in our VMAT plans, 5.2 ± 0.9 Gy, while it was 13.5 ± 5.0 Gy according to Zhang [ 17 ], 7.2 ± 2.3 Gy according to Zhao [ 18 ], 9.31 ± 1.62 Gy according to Hu [ 19 ], 11.9 ± 5.06 Gy according to Ma [ 20 ], 7.7 ± 1.1 Gy according to Xie [ 21 ] and 7.4 ± 1.4 Gy according to Wang [ 22 ],15.2 ± 2.2 Gy according to Nobnop [ 24 ], 9.3 ± 1.1 Gy according to Zhang [ 26 ]. The low and medium doses received by the heart were also significantly lower with the VMAT technique than with the IMRT technique, except for V 2.5 .…”
Section: Discussioncontrasting
confidence: 50%
“…The results of our study indicated that both IMRT and VMAT provided good coverage of the target, while VMAT showed, with statistical significance, more conformity and more dose homogeneity in the target area of CW and IMN, compared with those of IMRT, by avoiding areas of under-dose, and at the same time eliminating areas of relative overdose. Our VMAT significantly reduced the near-maximum dose of the PTV of CW and IMN, which was 54.3 ± 0.2 Gy, as compared with 55.4 ± 1.7 Gy from a study by Zhang [ 17 ], and 56.64 ± 0.63 Gy from a study by Hu [ 19 ], 54.93 ± 0.87 Gy from a study by Ma [ 20 ]. Furthermore, the increase in the near-minimum doses, V 95% and V 100% were higher in the VMAT plans than in the IMRT plans: 48.7 ± 0.3 Gy, as compared with 48.5 ± 2.2 Gy from a study by Zhang [ 17 ], and 48.84 ± 0.41 Gy from a study by Hu [ 19 ] and 47.77 ± 0.35 Gy from a study by Ma [ 20 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Historically, breast radiotherapy treatment planning consisted of two-dimensional planning, used a fluoroscopic technique to establish treatment fields. This was followed by 3-D CRT with two conventional tangential radiotherapy fields [5].…”
Section: Issn: 2320-5407mentioning
confidence: 99%